Fine-scale movements and habitat use of the Southern Ground Hornbill Bucorvus Leadbeateri - Zoghby, Blair Anthony (Percy FitzPatrick Institute of African Ornithology, 2015)
Southern Ground-Hornbills Bucorvus leadbeateri are listed as Endangered in South Africa and there is a concerted effort to reverse their population decline. Understanding the factors affecting their movement patterns and how they interact with their habitat is useful to inform conservation and habitat management options for the species, to select sites for artificial nests and to identify suitable areas for reintroduction initiatives. In this study, I report daily and seasonal patterns of habitat use as well as patterns of roost site use of four Southern Ground-Hornbill groups in the Associated Private Nature Reserves, northeast South Africa, based on data from GPS-satellite tags collected over one year from October 2010 to September 2011. Home ranges varied from 5.9-10.3 km² and were larger in winter than during the summer breeding season. Daily travel distances were greater during the breeding season, when birds were constrained to forage close to their nest, and were lower in winter, when birds ranged more widely. Hourly travel distances were affected by time of day, season, air temperature and group. Birds travelled farthest per hour in the morning, decreasing in the afternoon in winter. However, in summer hourly travel distances were bimodally distributed, with a minimum during the middle of the day when ambient temperatures exceed 25⁰C. Acacia-dominated vegetation and riparian habitats were favoured disproportionately during the heat of the day in summer, presumably because they offer more shade than other habitats. The number of roost sites used per month decreased progressively throughout the Early Wet season (October-December) and was lowest during the Late Wet season (January-March) for three groups that bred successfully. Mean monthly nights per roost were highest for these groups in the Early Wet and Late Wet seasons, specifically over December and January, coinciding with the peak breeding period. Throughout the Early Wet season, all four groups frequently roosted in close proximity to the nest, with 54-83% of roosts being within 1 000 m of the nest. During the Wet season, riparian habitats were favoured for roosting by the three groups that bred successfully, while during the dry season, disturbed areas, combretum-dominated habitats and mopane-dominated habitats were used. I conclude that the optimal habitat configurations for ground-hornbills include a mosaic of habitat types, including open areas for foraging and dense trees for shade as well as adequate large trees for nesting and roosting, particularly in riparian habitats.